RETRACTED: Modernisation of the Ponsse Ergo SMRM articulated joint at Mobile Service LLC - Svoykin F.V.; Svoykin V.F.; Maksimov P.P.; Poberezhskiy S.Y. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001